A Study on Technology Acceptance Model for Using Learning Management System (LMS) Among University Students: Empirical Study from a Private University in Bogor - Hari Suryantoro; Yayan Hadiyat (Journal of Social Transformation and Regional Development, 2024)
Internet-based online learning models are an option for more effective and efficient learning. The use of the Learning Management System (LMS) application in university education has become mandatory following the Covid-19 pandemic. This research aims to investigate the Technology Acceptance Model (TAM) in analyzing students' perceptions, attitudes, and behavior regarding the acceptance and use of LMS. The goal is to provide recommendations for enhancing the effectiveness of learning outcomes in higher education. This research was conducted at a private university (PTS) in Bogor by taking a random sample of 720 respondents from a population of 2,212 new students with a sampling error of 5%. The research results show that technology acceptance factors follow the process as described in attitude theory and the theory of planned behavior. The willingness to use the LMS well is greatly influenced by the cognitive processes that students receive in building their perception of ease and usefulness in accepting technology in learning.